PEMBERIAN PAKAN IKAN NILA (Oreochromis niloticus) DENGAN PENAMBAHAN EKSTRAK ETANOL TEPUNG RUMPUT LAUT (Kappaphycus alvarezii) PADA PERBANDINGAN KONSENTRASI PELARUT YANG BERBEDA - Salnida Yuniarti Lumbessy; Tri Wahyunyngsyh; Zaenal Abidin (Universitas Muhammadiyah Gresik, 2024)
This study aims to analyze the effect of providing commercial feed with the addition of ethanol extract of K. alvarezii seaweed flour on the growth of tilapia (O. niloticus). The research was carried out in July – October 2023 at the Aquaculture Reproduction Laboratory, Faculty of Agriculture, Mataram University. The method used in this study was an experimental method using a completely randomized design with 4 treatments and 3 replications, namely : commercial feed (control/P1), 96% ethanol extract 1:3 (P2), 96% ethanol extract 1:4 (P3), and ), 96% ethanol extract 1:5 (P4). Extraction was carried out by macerating K. alvarezii seaweed flour for 30 hours, then filtering and evaporating at 40 oC until an extract was produced in liquid form. The extract is mixed with feed at a rate of 2 g/kg feed. Before being given to feed, the extract is mixed first with 10 ml of distilled water. The tilapia seeds used measure 4 – 5 cm with a stocking density of 1 fish/liter. Fish rearing is carried out for 50 days, with a feeding frequency of 5% of the total weight of the fish and done 3 times a day. The test parameters are absolute weight, absolute length, specific growth rate (SGR), feed conversion (FCR), feed utilization efficiency, survival (SR) and water quality, which includes temperature, pH and DO. Data were analyzed using ANOVA and Duncan test at significant level of 0.05. The research results showed that the addition of K. alvarezii ethanol extract to tilapia feed can influence growth, feed utilization efficiency, feed convention rate (FCR), and survival rate (SR) of tilapia. The addition of K. alvarezii ethanol extract 1:5 to the feed showed the best results because it could increase the growth and utilization of tilapia feed with a survival rate of tilapia of 83%.